Orally Administered Docetaxel-Loaded Chitosan-Decorated Cationic PLGA Nanoparticles for Intestinal Tumors: Formulation, Comprehensive in Vitro Characterization, and Release Kinetics - Unal, Sedat; Dogan, Osman; Aktas, Yesim (Beilstein-Institut, 2022)
Intestinal cancers are the third most lethal cancers globally, beginning as polyps in the intestine and spreading with a severe meta-static tendency. Chemotherapeutic drugs used in the treatment of intestinal tumors are usually formulated for parenteral administra-tion due to poor solubility and bioavailability problems. Pharmaceutically, clinical failure due to a drug's wide biodistribution and non-selective toxicity is one of the major challenges of chemotherapy. In addition, parenteral drug administration in chronic diseases that require long-term drug use, such as intestinal tumors, is challenging in terms of patient compliance and poses a burden in terms of health economy. Especially in the field of chemotherapy research, oral chemotherapy is a subject that has been inten -sively researched in recent years, and developments in this field will provide serious breakthroughs both scientifically and socially. Development of orally applicable nanodrug formulations that can act against diseases seen in the distant region of the gastroin-testinal tract (GIT), such as intestinal tumor, brings with it a series of difficulties depending on the drug and/or GIT physiology. The aim of this study is to develop an oral nanoparticle drug delivery system loaded with docetaxel (DCX) as an anticancer drug, using poly(lactic-co-glycolic acid) (PLGA) as nanoparticle material, and modified with chitosan (CS) to gain mucoadhesive properties. In this context, an innovative nanoparticle formulation that can protect orally administered DCX from GIT conditions and deliver the drug to the intestinal tumoral region by accumulating in mucus has been designed. For this purpose, DCX-PLGA nanoparticles (NPs) and CS/DCX-PLGA NPs were prepared, and their in vitro characteristics were elucidated. Nanoparticles around 250-300 nm were obtained. DCX-PLGA NPs had positive surface charge with CS coating. The formulations have the potential to deliver the encapsulated drug to the bowel according to the in vitro release studies in three different simulated GIT fluids for approximately 72 h. Mucin interaction and penetration into the artificial mucus layer were also investigated in detail, and the mucoadhesive and mucus-penetration characteristics of the formulations were examined. Furthermore, in vitro release kinetic studies of the NPs were elucidated. DCX-PLGA NPs were found to be compatible with the Weibull model, and CS/DCX-PLGA NPs were found to be compatible with the Peppas-Sahlin model. Within the scope of in vitro cytotoxicity studies, the drug-loaded NPs showed signifi-cantly higher cytotoxicity than a DCX solution on the HT-29 colon cell line, and CS/DCX-PLGA showed the highest cytotoxicity (p < 0.05). According to the permeability studies on the Caco-2 cell line, the CS/DCX-PLGA formulation increased permeability by 383% compared to free DCX (p < 0.05). In the light of all results, CS/DCX-PLGA NPs can offer a promising and innovative ap-proach as an oral anticancer drug-loaded nanoformulation for intestinal tumors.
Aktas, Yesim/0000-0002-3427-6078; Unal, Sedat/0000-0002-1518-010X; Dogan, Osman/0000-0003-2314-6793; Osman, Dogan/0009-0006-9810-2698
Keywords: Chitosan; Docetaxel; Intestinal Tumors; Oral Drug Delivery; Plga